Teaching Strategies for Microplastic Material in Science Learning: Literature Review - Siti Apriliyanti Khodijah; Eli Rohaeti (Jurnal Penelitian Pendidikan IPA, 2025)
Waste is one of the polemic problems that occurs in Indonesia. Almost every region has savings in the form of waste in large amounts and is spread throughout Indonesia. Not a few people do not care about the use of plastic waste which can cause environmental pollution. This study highlights the teaching of microplastic material, a new global environmental problem, in science learning. The novelty lies in the emphasis on topics that are relevant to current environmental conditions and offer innovative learning strategies, such as project-based methods, experiments, and digital technology, to improve students' understanding. This research aims to analyze science learning strategies in integration with microplastics. The method used in this research is a literature review using the PRISMA approach. The data source was taken from Sinta 1-3 via the Google search engine over the last 6 years. The results of the review found that the learning model most frequently used as Problem Based Learning (PBL), then the second most frequently used was the Guided Inquiry model. These two learning models are often used because they are most relevant to the nature and complexity of environmental problems, while the learning model that is rarely used is the Discovery Learning model because this model gives students the freedom to find information independently so that if students are not guided it will cause unnecessary misunderstandings. adequate regarding environmental pollution problems.